Yoga as an Alternative and Complementary Approach for Arthritis - Manoj Sharma MBBS, MCHES, PhD, FAAHB (SAGE Publishing, 2014)
In the United States, approximately 21% of the adults suffer from arthritis. Yoga offers one possible way of managing arthritis. The purpose of this study was to look at studies from 2010 to June 2013 and examine whether yoga can be an efficacious approach for managing arthritis. A systematic search from Medline, Cumulative Index to Nursing and Allied Health, and Alt HealthWatch databases was conducted for quantitative articles involving all schools of yoga. A total of 9 articles met the inclusion criteria. Five of these were from the United States and 4 from India. Of the 9 studies, 6 demonstrated positive changes in psychological or physiological outcomes related to arthritis. Despite the limitations not all studies using randomized controlled design, having smaller sample sizes, having different outcomes, having nonstandardized yoga intervention, not using behavioral theory, and having varying lengths, yoga appears to be a promising modality for arthritis.